Participation in the age of globalization and information - Kalmi, Panu; Klinedinst, Mark (Emerald, 2006)
This volume of Advances in the Economic Analysis of Participatory and Labor-Managed Firms consists of twelve original and innovative articles. The first four papers relate to the growing literature on employee participation and firm performance. The second group of papers looks at the impact of ownership structures into managerial compensation and control. The third set of papers analyzes the role of co-operatives in the changing economic environment. The three papers in the final section range from the historical perspective on participation to the role different forms of participation may play in the future. Together, these papers draw on the expertise of a number of leading thinkers in the area and promise the reader a challenge to help deliver practical policies to transform our work world and society. The series: is international in scope; and fills substantial gap in this field. Although its primary focus is economic, the editors welcome analytical studies from related fields.
Keywords: Management -- Employee participation.; Industrial management -- Employee participation.; elektronické knihy; electronic books